1998
DOI: 10.1016/s1074-7613(00)80664-0
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Receptor Maintains Lymphoid Homeostasis by Supporting Lymphocyte Homing and Proliferation

Abstract: The IL-15 receptor alpha subunit (IL-15Ralpha) mediates high-affinity binding of IL-15, a pleiotropic cytokine implicated in the development of innate immune cells. We have generated IL-15Ralpha null (IL-15Ralpha-/-) mice to understand the role of IL-15Ralpha in immune development and function. IL-15Ralpha-/- mice are markedly lymphopenic despite grossly normal T and B lymphocyte development. This lymphopenia is due to decreased proliferation and decreased homing of IL-15Ralpha-/- lymphocytes to peripheral lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
1,050
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,170 publications
(1,121 citation statements)
references
References 31 publications
58
1,050
0
2
Order By: Relevance
“…Although the importance of IL-15 in this process is undisputed [19,20,[22][23][24], it is unclear whether IL-15 1) acts on early NK cell precursors, 2) is only needed at the terminal steps of NK cell development or 3) is important role in maintaining lymphocyte proliferation and homeostasis. To investigate this process, we cultured human umbilical cord blood (UCB) CD34 + Lin − CD38 − primitive progenitors on AFT024.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the importance of IL-15 in this process is undisputed [19,20,[22][23][24], it is unclear whether IL-15 1) acts on early NK cell precursors, 2) is only needed at the terminal steps of NK cell development or 3) is important role in maintaining lymphocyte proliferation and homeostasis. To investigate this process, we cultured human umbilical cord blood (UCB) CD34 + Lin − CD38 − primitive progenitors on AFT024.…”
Section: Resultsmentioning
confidence: 99%
“…IRF-1 knockout mice exhibit a severe NK deficiency, which is mediated by failure of transcriptional regulation of IL-15. In addition, knockout mice deficient in IL-15 itself or IL-15Rα have very few NK cells while IL-2 and IL-2Rα knockouts are unaffected [19,20]. In human studies, IL-15 is made by stroma and macrophages [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, mice deficient for signalling components of IL-7 and IL-15 (IL-7Ra À/À IL-2Rb À/À display a thymopoiesis block more closely resembling that of g c À/À mice than mice deficient for signalling components of IL-7 and IL-2 (IL-7Ra À/À IL-2Ra À/À ) or IL-7 and IL-4 (IL-7Ra À/À IL-4Ra À/À ) [39]. That fact that mice deficient for IL-15 or IL-15Ra display no obvious abnormalities in thymopoiesis [20,21] suggests a minor role for IL-15 in this species that is only evident when thymopoiesis is already impaired (such as in the absence of IL-7). The bioactive form of IL-15 is complexed with the IL-15Ra chain.…”
Section: Discussionmentioning
confidence: 99%
“…While IL-15 does not appear essential for thymopoiesis in mice [20,21], previous studies have shown that TEC subsets express IL-15 [22] and could ''trans-present'' IL-15/IL-15Ra complexes to developing thymocytes [23,24]. Since the bioavailability of human IL-15 in HIS mice appears limited [3], we next investigated the effect of exogenous IL-15 on human thymopoiesis in vivo.…”
Section: Effects Of Exogenous Human Il-15 Administration On Human Thymentioning
confidence: 99%